Determinan Kematian Neonatal Pada Bayi Berat Lahir Rendah di Indonesia (Analisis Data SDKI 2002-2003 dan 2007) - Izza Suraya (UHAMKA Press, 2017)
Determination of Neonatal Death in Low Birth Weight Infants in Indonesia (Data Analysis of IDHS 2002-2003 and 2007) Introduction. There were 72.4% infants with less than 2.500 grams Low Birth Weight (LBW) babies diedin their neonatal period in Indonesia. An understanding of all factors that influenced the neonatal deathis important. Therefore, this study was conducted to identify factors of LBW neonatal death between 1997and 2007. Methods. Based on 2002-2003 and 2007 Indonesia Demographic Health Survey, 1,232 LBW babies areselected. The design of study was cohort prospectif with cox proportional hazard analysis to measure therelationship between neonatal death and its determinants maternal, infant, health care, and mother’ssocial demographic. Resuls. After controlling all the variables, the result showed that neonatal death in LBW babiesdeteriminants are immediate breastfeeding, birth weight, sex, the term of birth, complications duringpregnancy, delivery complications, birth attendance, type of delivery, place of delivery, wealth index, andmother’s education. Variable that showed strongest risk association is complications during pregnancywith HR = 4.12 (95 % CI : 0.64- 26,65; p value = 0.307). Meanwhile, the strongest of protectiveassociation is middle class on wealth index variable. Conclusions. The study concluded that birth weight influences the incidence of neonatal death.Determinant that have the greatest effect on neonatal death is complications during pregnacy. Infantswho born from middle-class economic categories are the most protective factor to avoid neonatal deathsamong other wealth indexes.